Socio-Cultural and Educational Impacts of Menstrual Hygiene Management: A Synthesis of Evidence from Nepal and Broader Contexts - Dhital, Krishna Prasad (NPRC Journal of Multidisciplinary Research, 2025)
Background: Menstrual Hygiene Management (MHM) is a significant public health issue that intersects with education, gender equality, and human rights. In many low- and middle-income countries, socio-cultural norms and a lack of resources create substantial barriers for adolescents. Objective: This review synthesizes recent evidence on the socio-cultural and educational impacts of inadequate MHM, with a specific focus on findings from Nepal, to provide context-specific and actionable recommendations. Methods: A systematic literature review was conducted using Google Scholar, Semantic Scholar, and PubMed. The search included key terms such as "menstrual hygiene management Nepal," "cultural taboos menstruation," "school absenteeism," and "menstrual knowledge." Priority was given to peer-reviewed articles published between 2018 and 2024. Results: The synthesis reveals that profound cultural stigmas and restrictions during menstruation are pervasive, leading to fear, shame, and isolation among girls. Knowledge about menstruation is often inadequate before menarche, sourced primarily from friends and mothers with limited understanding. These factors, combined with poor school WASH facilities, directly contribute to high rates of school absenteeism, with girls reporting concentration difficulties and a decline in academic performance during their periods. Conclusion: Inadequate MHM severely constrains the educational opportunities and psychosocial well-being of adolescent girls. Effective interventions must be multi-pronged, addressing deep-seated cultural taboos through comprehensive education, improving water, sanitation, and hygiene (WASH) infrastructure in schools, and ensuring access to affordable menstrual products.